Elementary School Students' Mathematical Disposition Ability Oriented with STEAM Approach - Rahma Hidayanthi; Yanti Fitria; Hendra Syarifuddin; Yalvema Miaz (International Journal of Elementary Education, 2022)
Student's interest, persistence, and tendency in learning mathematics were still low. This is because students have learning difficulties and are not interested in mathematics. To develop solid mathematical habits, students need a mathematical disposition to study mathematics. This study aims to analyses how the STEAM approach affected primary school students' disposition for mathematics. The sort of research used in this study was quantitative research using experimental techniques. The Nonequivalent Control Group Design is used in this study. The population of this study comprised fifth-grade primary school children. Class VA served as the experimental class for this study, and class VB served as the control class. A questionnaire is an instrument utilized in this study. The analysis used is independent sample t-test, normality and homogeneity tests. The result found that the application of the STEAM approach has a significant effect on the mathematical disposition of class students on speed and discharge according to the results of the t-test analysis which has a significance value. Learning with the STEAM approach makes students play an active role in learning activities.